An experimental and simulation study of the role of thermal effects on variability in TiN/Ti/HfO2/W resistive switching nonlinear devices. (July 2022) - Maldonado, D.; Aguilera-Pedregosa, C.; Vinuesa, G.; García, H.; Dueñas, S.; Castán, H.; Aldana, S.; González, M.B.; Moreno, E.; Jiménez-Molinos, F.; Campabadal, F.; Roldán, J.B.
Abstract: An in-depth simulation and experimental study has been performed to analyze thermal effects on the variability of resistive memories. Kinetic Monte Carlo (kMC) simulations, that reproduce well the nonlinearity and stochasticity of resistive switching devices, have been employed to explain the experimental results. The series resistance and the transition voltages and currents have been extracted from devices based on the TiN/Ti/HfO2 /W stack we have fabricated and measured at temperatures ranging from 77 K to 350 K. We observed that the variability for all the magnitudes analyzed was much higher at low temperatures. In the kMC simulations, we obtained conductive filaments (CFs) with less compactness at low temperatures. This led us to explain the higher variability, based on the variations of the CF morphology and density seen at low temperatures.